2017
DOI: 10.1287/mnsc.2016.2531
|View full text |Cite
|
Sign up to set email alerts
|

Market Mechanisms in Online Peer-to-Peer Lending

Abstract: O nline peer-to-peer lending (P2P lending) has emerged as an appealing new channel of financing in recent years. A fundamental but largely unanswered question in this nascent industry is the choice of market mechanisms, i.e., how the supply and demand of funds are matched, and the terms (price) at which transactions will occur. Two of the most popular mechanisms are auctions (where the "crowd" determines the price of the transaction through an auction process) and posted prices (where the platform determines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
107
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(107 citation statements)
references
References 39 publications
0
107
0
Order By: Relevance
“…A variety of literature has made efforts to delve into the forms of crowdfunding, such as an equity purchase, loan, or pre-order on a product [48][49][50][51][52], or the economic mechanisms of peer-to-peer lending [15,[53][54][55]. For example, Wei and Lin [15] both theoretically and empirically investigated how the supply and demand of funds in online peer-to-peer lending markets are matched, and the prices at which transactions will occur. They concluded that, under platform-mandated posted prices, loans are funded with high probability, but at the same time with relatively high preset interest rates.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A variety of literature has made efforts to delve into the forms of crowdfunding, such as an equity purchase, loan, or pre-order on a product [48][49][50][51][52], or the economic mechanisms of peer-to-peer lending [15,[53][54][55]. For example, Wei and Lin [15] both theoretically and empirically investigated how the supply and demand of funds in online peer-to-peer lending markets are matched, and the prices at which transactions will occur. They concluded that, under platform-mandated posted prices, loans are funded with high probability, but at the same time with relatively high preset interest rates.…”
Section: Related Literaturementioning
confidence: 99%
“…In fact, financing difficulty of small and micro businesses is universal across the world for both developing and developed countries, which has been documented by substantial research [6][7][8][9]. On the other hand, rare literature directly explores the relationship between the use of the Internet and individual or firms' access to external finance, although a strand of literature [10][11][12][13][14][15] has investigated the influence of online peer-to-peer lending as an appealing new channel of financing on people's economic behavior. This study attempted to fill the void in the environment of an emerging economy, China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has been conducted on P2P market interest rates, including the pricing mechanism (Wei and Lin, 2016), marketization (Liao et al, 2014), discrimination (Pope and Sydnor, 2011) and social relations (Lin et al, 2013;Freedman and Jin, 2017). Previous studies on the determinants or influencing factors of P2P interest rates were mostly conducted from within the market and mainly focused on the micro characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And, it is meaningful to explore the correlation of participants' attentions in the whole private lending market in China. Recent research on the private lending market system mainly includes (1) the related research on the P2P lending market, such as borrowing success rate and default rate [14][15][16][17][18], investor behavior [19][20][21][22], and credit evaluation and market mechanism [23][24][25][26][27][28]; (2) the relationship between the informal credit market and the formal credit market [6,[29][30][31][32]; and (3) the research on offline loan [33][34][35]. erefore, this paper expands the research scope of the existing literature by investigating the extent of interdependence across time to clarify whether participants' attentions to P2P lending and offline loan are segmented or becoming more integrated.…”
Section: Introductionmentioning
confidence: 99%